Compensator Based Perfromance Enhancement Strategy for a SIQO Buck Converter - Augusti Lindiya; S Palani; K Vijayarekha (Institute of Advanced Engineering and Science, 2016)
This paper attempts to design lag and lag-lead compensators for improving the performance of a Single Inductor Quad Output (SIQO) dc-dc buck converter in terms of time domain and frequency domain specifications. It develops the state space averaged model to find the duty ratio of the desired output voltages at steady state. The exercise arrives at the transfer function model from the state space averaged model through the use of its lumped small signal equivalent circuit which allows analyzing the performance of the system in frequency and time domains. The responses are derived in the MATLAB/Simulink® using discrete components incorporating compensators of the converter. The hardware results obtained using Data Acquisition Module DT9834® interfaced to MATLAB/Simulink® and prototype model establish the performance of the compensator based converter and further emphasize its ability to minimize the ripples over a range of operating loads.